Rozdział 6b. Der Verein MiKK e.V. – Mediator: innen und Dialog ohne Grenzen - Jańczuk, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
MiKK – International Mediation Centre for Family Conflict and Child Abduction, is the leading international specialist in the field of cross-border family mediation. MiKK is an internationally recognized, neutral and independent NGO based in Berlin. For almost 20 years MiKK has been helping families from all over the world to find amicable solutions on all issues surrounding international custody disputes as well as child abduction cases. MiKK sets up and organizes multi-lingual mediations in any country for parents who wish to try and resolve their dispute by way of mediation in the best interest of their child. Courts, Lawyers, Embassies, Ministries of Justice/Central Authorities from all over the world refer parents to MiKK. MiKK also trains mediators in the field of cross-border family mediation and arranges the first contact between mediators and parents. There are currently more than 170 multilingual mediators worldwide who mediate in more than 30 languages. This article gives an overview and important information about MiKK’s work. It will also present the organisational solutions developed by the organisation that could be replicated in other European countries. It briefly describes MiKKs cooperation and referral of mediators as well as the organisation’s cooperation with national and international authorities.
Keywords: mediator; kwalifikacje; mediacje transgraniczne; mediacje rodzinne; komediacje; MiKK